2016
DOI: 10.1126/scitranslmed.aaf1471
|View full text |Cite
|
Sign up to set email alerts
|

Familial autoinflammation with neutrophilic dermatosis reveals a regulatory mechanism of pyrin activation

Abstract: Pyrin responds to pathogen signals and loss of cellular homeostasis by forming an inflammasome complex that drives the cleavage and secretion of IL-1β. We studied a family with dominantly inherited autoinflammatory disease characterised by childhood-onset recurrent episodes of neutrophilic dermatosis, fever, elevated acute-phase reactants, arthralgia, and myalgia/myositis. Disease was caused by a mutation in MEFV, the gene encoding pyrin (S242R). The clinical distinction from FMF, also caused by MEFV mutation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
275
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(289 citation statements)
references
References 31 publications
(32 reference statements)
8
275
1
5
Order By: Relevance
“…Importantly, the B30.2 domain is absent in the murine Pyrin ortholog, which prompted us to characterize regulation mechanisms of Pyrin activation in peripheral blood mononuclear cells (PBMCs) of healthy donors in parallel with studies in murine bone marrow-derived macrophages (BMDMs). As reported (14,15), TcdB activated the Pyrin inflammasome in our studies ( Fig. S1 A and B).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Importantly, the B30.2 domain is absent in the murine Pyrin ortholog, which prompted us to characterize regulation mechanisms of Pyrin activation in peripheral blood mononuclear cells (PBMCs) of healthy donors in parallel with studies in murine bone marrow-derived macrophages (BMDMs). As reported (14,15), TcdB activated the Pyrin inflammasome in our studies ( Fig. S1 A and B).…”
Section: Resultssupporting
confidence: 88%
“…Dephosphorylation of Pyrin's intermediate linker domain was recently shown to be required for TcdA-and TcdB-induced inflammasome activation (14,15,19), and introduction of FMF mutations in the B30.2 domain of ectopically expressed Pyrin did not interfere with this process (15). In agreement with these reports, we showed that endogenous Pyrin was not constitutively active in FMF PBMCs but was engaged only after TcdA stimulation or C. difficile infection ( Fig.…”
Section: Fmf-associated Pyrin Binds Tubulin But Does Not Require Micrsupporting
confidence: 91%
See 1 more Smart Citation
“…49,50 FMF-associated mutations in the B30.2 domain inhibit the interaction between pyrin and protein kinase N1, and reduce the inhibitory control on pyrin activation. 49 Our work, along with the earlier-mentioned findings, define the upstream molecular mechanisms involved in IL-1b release during FMF pathogenesis.…”
Section: Caspase-1 Mediated Il-1b Drives Fmfmentioning
confidence: 99%
“…MEFV geni üzerinde bugüne kadar tanımlanmış olan mutasyonlar Tablo 1'de verilmiştir (5). MEFV geninde meydana gelen mutasyonlar, pyrin ekspresyonunu azaltır ve interlökin (IL)-1β'yı aktive eden kaspaz-1 enflamasyon kontrol mekanizmasındaki işlevini yerine getiremediğinden uyarılmış olan enflamasyon durdurulamaz (6). Pyrin proteininin IL-1β işlenmesini engellemesi ve makrofaj apoptozuna izin vermesi, fonksiyonel olarak antienflamatuvar bir molekül olduğunu göstermektedir.…”
Section: Introductionunclassified